Effect of Seed Rate on Seedling Quality for Mechanical Rice Transplanting - Hossen, MA; Hossain, MM; Haque, ME; Bell, RW (Bangladesh Rice Journal, 2019)
A study was conducted in the Farm Machinery and Postharvest Technology Division, Bangladesh Rice Research Institute (BRRI), Gazipur in the irrigated dry season (Boro) of 2012-13. It was aimed at identifying the optimum seed rate of different graded rice variety for mat type seedlings preparation and suitable seedling adjustment option of the rice trans planter to maintain required number of seedlings dispensed per stroke by the rotary picker of the trans planter. Walk behind type 4-rows rice trans planter (DP 480) was used to conduct the study. The experiment was followed as two factorial completely randomized design (CRD) with three replications. Three categories of rice variety as short and bold grain (cv. BR3), medium and slender grain (cv. BRRI dhan28) and extra-long and slender grain (cv. BRRI dhan50) were considered as main factor whereas seed rate of 100, 120, 130, 140, 150 and 160g pertray (280×580×25 mm) were considered as sub-factor. Irrespective of rice category, seedling emergence decreased with the increase of seed rate. Seedling emergence decreased from 77 to 56, 74 to 57 and 77 to 54% in BR3, BRRI dhan28 and BRRI dhan29 respectively with the increase of seed rate from 100 to 160g per tray. Seed rate did not affect the seedling height significantly whereas it was varied with the rice verities only and BRRI dhan50 produced higher seedling length. However, number of leaf, stem thickness and shoot dry weight decreased and root-shoot ratio increased significantly with the increase of seed rate. The highest shoot dry weight was observed in BR3 followed by BRRI dhan50. Seedling strength also decreased with the increase of seed rate. The highest seedling strength (0.043 mg cm-1) was observed for the seed rate of 100g of BR3 and the lowest (0.020 mg cm-1) for the seed rate of 160g of BRRI dhan28. The number of seedling increased and percentage of missing hills decreased with the increase of both the seed rate and seedling adjustment option of the rice transplanter irrespective of variety. In case of BR3, seedling dispensed per stroke and percentage of missing hills varied from 4.3 to 5.7 and 6.8 to 7.8 for the seed rates of 140, 150 and 160 g of seeds tray-1 for 5 to 7 seedling adjustment option of the rice transplanter respectively. Seedlings per stroke and percentage of missing hills of BRRI dhan28 for the seed rate of 130, 140 and 150 g of seeds tray-1 was found almost same for 5 to 7 seedling adjustment options of the rice transplanter (4.2 to 6.3 and 5.7 to 9.8). However, there was minimum difference of seedlings per stroke and percentage of missing hills among 120, 130 and 140 g of seeds tray-1 for the option of 4 to 7 (4.0 to 5.6 and 3.9 to 7.8 respectively) for BRRI dhan50. It can be concluded that 140 g of seeds tray-1 for short and bold grain (BR3) and 130 g of seeds tray-1 for medium and slender grain (BRRI dhan28) under the seedling adjustment options of 5 to 7 and 120 g of seeds tray-1 for extra-long and slender grain (BRRI dhan50) under the seedling adjustment options of 4 to 7 may be used for desired seedlings per hill and minimum missing hills along with good quality of seedling. Bangladesh Rice j. 2018, 22(1): 9-23